THE CONDITION OF THE AMISH LIFE AND ENGLISHCHER CULTURE AS REFLECTED IN JODY PICOULT’S PLAIN TRUTH: A SOCIOLOGICAL APPROACH - Yudiati, Rini; Ach. Andiriyanto; Anni Annisa (Journal of Innovation Research and Knowledge, 2023)
The Condition of the Amish Life and Englischer Culture as Reflected in Jody Picoult’s plain truth”. It primarily intended to describe the Amish life portrait, Englischer culture, and how far the influence of the religious aspect to outsider world. The data of the study are taken through alibrary research that employs the descriptive technique to give clearer explanation of the problem statement. In this research, the writer employs sociological study to analyze the data. The main data of this research is taken from the novel “plain truth“ written by Jody Picoult and the source of data of this research becomes the primary source and secondary source. In relation to primary source the writer reads the novel carefully and critically. The secondary source the writer takes from the materials, which are relevant to support the analysis. The result of this study can be briefly stated as followers. The characters are presented by using the technique of telling story and it divided into major and minor characters; they are Ellie Hathaway, Katie Fisher, while the minor characters are Coop, Jacob Fisher, Aaron Fisher, Sarah of plain truth story is taken place mostly in Lancaster County, Paradise, Pennsylvania and a little in Philadelphia, Unites states at summer 2000. The Englischer or American culture as describe in the novel and basically each of them has different condition and treatment in every part of life